2018
DOI: 10.1177/1541931218621464
|View full text |Cite
|
Sign up to set email alerts
|

The Reality of Virtual Reality: A Comparison of Pedestrian Behavior in Real and Virtual Environments

Abstract: Virtual reality (VR) can be a very effective tool to evaluate built environment to support improvement of pedestrian and other vulnerable road user safety. However, in order to draw actionable conclusions from VR it is important to understand the degree to which pedestrians’ perceptions and behaviors match across real and virtual environments. In this study, participants experienced equivalent real and virtual environments and performed similar tasks in each. Tasks included pedestrian’ intention to cross, esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 11 publications
2
42
0
1
Order By: Relevance
“…This could have made it possible for the participants to make unsafe decisions which would not be found in real life crossing situations. However, Bhagavathula, Williams, Owens, and Gibbons (2018) revealed in a similar study where pedestrians' crossing behavior in virtual environments was compared with their behavior in a real life experiment that the decisions made in real life and in virtual reality are similar. This is an indication of the validity of this method but future research comparing this smartphone and 360 degrees videos-based VR method with other kinds of VR methods and field studies could assess its performance more clearly.…”
Section: Involvementmentioning
confidence: 93%
“…This could have made it possible for the participants to make unsafe decisions which would not be found in real life crossing situations. However, Bhagavathula, Williams, Owens, and Gibbons (2018) revealed in a similar study where pedestrians' crossing behavior in virtual environments was compared with their behavior in a real life experiment that the decisions made in real life and in virtual reality are similar. This is an indication of the validity of this method but future research comparing this smartphone and 360 degrees videos-based VR method with other kinds of VR methods and field studies could assess its performance more clearly.…”
Section: Involvementmentioning
confidence: 93%
“…Therefore, it usually requires the least immersive environment such as wall-based or monitor-based projection with special goggles or HMD with a simple input devices like keyboard, mouse, touchscreen or controller. Generally such scenarios consist of 3D visualisation [39,42], training in hazardous situation [43][44][45] as well as travel and space trips [46,47]. Very good examples are presented in [47], where the author summarises the impact of VR on history education.…”
Section: Types Of Virtual Educational Environmentsmentioning
confidence: 99%
“…Some studies have started to compare reallife pedestrian behavior to the behavior observed in virtual environments. For example, several studies investigate whether virtual experiments can be used to capture the roadcrossing behavior of pedestrians in the presence of vehicles and generally find a good match to real-life behavior (Bhagavathula et al, 2018;Deb et al, 2017;Schwebel et al, 2008). Other research confirms that simple avoidance maneuvers between pedestrians can also be faithfully captured in virtual experiments (Iryo-Asano et al, 2018;Moussaid et al, 2016).…”
Section: Introductionmentioning
confidence: 99%